The Drosophila Arf GEF Steppke controls MAPK activation in EGFR signaling. - Hahn, I.; Fuss, B.; Peters, A.; Werner, T.; Sieberg, A.; Gosejacob, D.; Hoch, M. (Journal of Cell Science, 2013)
Guanine nucleotide exchange factors (GEFs) of the cytohesin protein family are regulators of GDP/GTP exchange for members of the ADP ribosylation factor (Arf) of small GTPases. They have been identified as modulators of various receptor tyrosine kinase signaling pathways including the insulin, the vascular epidermal growth factor (VEGF) and the epidermal growth factor (EGF) pathways. These pathways control many cellular functions, including cell proliferation and differentiation, and their misregulation is often associated with cancerogenesis. In vivo studies on cytohesins using genetic loss of function alleles are lacking, however, since knockout mouse models are not available yet. We have recently identified mutants for the single cytohesin Steppke (Step) in Drosophila and we could demonstrate an essential role of Step in the insulin signaling cascade. In the present study, we provide in vivo evidence for a role of Step in EGFR signaling during wing and eye development. By analyzing step mutants, transgenic RNA interference (RNAi) and overexpression lines for tissue specific as well as clonal analysis, we found that Step acts downstream of the EGFR and is required for the activation of mitogen-activated protein kinase (MAPK) and the induction of EGFR target genes. We further demonstrate that step transcription is induced by EGFR signaling whereas it is negatively regulated by insulin signaling. Furthermore, genetic studies and biochemical analysis show that Step interacts with the Connector Enhancer of KSR (CNK). We propose that Step may be part of a larger signaling scaffold coordinating receptor tyrosine kinase-dependent MAPK activation.